Structural and luminescence properties of europium oxide and dysprosium oxide codoped strontium borophosphate ceramics [electronic resource - Leong, Pau Ming, 1989- , author (2015)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2015